L’activité collective, processus organisant : un processus discursif fondé sur le langage pragmatiste des habitudes - Philippe Lorino (Activités)
Recent streams in organization research have developed an action-based view of organizing, whereby actors’ actions make organization emerge as a dynamic construct. They stress the process by which discourses make the sense of action emerge and generate "organizing" practical effects. This article adopts the symmetric view, focused on activity itself as a discourse in acts, rather than on language practices and objects which are involved in activity. Echoing the theory of “speech acts” (Austin, 1970 ; Searle, 1971) which explores the “performativity of discourse”, i.e. its power of transforming situations, this article sketches a theory of “act speeches”, exploring the “discursivity of action”, i.e. its power to make meaning. Acts are not only operations which transform the situation, but also signs pointing at socially constructed meanings. Resorting to the pragmatist theories of habit (Peirce, 1931-1958, 1992; Dewey, 1922-1957) and inquiry (Peirce, 1992 ; Dewey, 1938-1980), collective activity is analyzed as a discursive process, combining stabilized and socially shared segments of signification (“habits”) and situated inquiries to adapt or recreate habits. A case study (implementation of an integrated management information system in a large firm) shows that major organizational changes may reveal habits and their discursive coherence by disturbing them. Actors face the task, difficult because unanticipated, of rebuilding the discursive frames of their collective activity. The conclusion summarizes the theoretical, practical and methodological contributions of this approach to activity.